Optical feedback laser absorption spectroscopy of N2O at 2 µm. (October 2020) - Odintsova, T.A.; Fasci, E.; Gravina, S.; Gianfrani, L.; Castrillo, A.
Abstract : highlights: We present an optical-feedback laser absorption spectrometer (OF-LAS), operating at 2 µm wavelength and assisted by an optical frequency comb. We used a multispectrum fitting approach involving the uncorrelated and symmetric version of the Hartmann-Tran profile. Evidence for multiple non-Voigt mechanisms affecting the experimental spectra was found. We retrieved line intensity factors with an overall uncertainty within 0.38%. We also determined self-broadening coefficients, speed dependence components of the collisional line broadening, and Dicke narrowing parameters. We compared the measured line intensities with those from HITRAN and NOSD-1000 databases. The agreement is more satisfactory for the NOSD-1000 rather than HITRAN. Abstract: We present high-accuracy measurements of the spectroscopic parameters of eight nitrous oxide transitions, mainly belonging to the P branch of the 3 ν 1 + 2 ν 2 vibrational band, in the spectral region around 4982 cm − 1 . We acquired absorption spectra in pure N2 O samples, at room-temperature, by means of a diode laser based spectrometer in which the laser emission width was effectively narrowed by exploiting the optical feedback from a V-shaped high-finesse cavity. The spectrometer was assisted by a self-referenced optical frequency comb synthesizer for frequency calibration purposes. Light absorption from N2 O molecules occurred inside a multiple reflections cell, which was placed on the transmission from the cavity. The successful application of a global fitting approach to a manifold of spectra, involving the symmetric uncorrelated version of quadratic speed-dependent hard collision profile, allowed us to determine line intensities with an overall relative uncertainty of 0.38%. We found a satisfactory agreement with data provided by the HITRAN and NOSD-1000 databases. Self-broadening coefficients, speed dependence components of the collisional line broadening, and Dicke narrowing parameters were also determined.